SCIENTIFIC FUNGAL REPORT OF MOLDY JEANS IN INDONESIA - Ivan Permana Putra (Universitas Tadulako, 2020)
Mold are multicelular -microscopic fungi known as heterotrophic-cosmopolitan organism which exist almost at any place in the environment. Textiles, particularly those composed of natural organic such as jeans are easily colonized by mold. Till time, there is no report ever found regarding fungal of moldy jeans in Indonesia. This study aimed to isolate fungi from moldy jeans, identified, and described it. The result revealed that the isolate studied was Chaetomium globosum, by using several macroscopic and microscopic characters. However, since Chaetomium are known as species complex fungi, further observation is needed using molecular approach. Therefore, author consider that the isolate should be treated as Ch. globosum sensu lato for time being. Interestingly, Ch. globosum was frequently reported as endophytic fungi, which pose the potency to be used as biocontrol and bioinducer in agriculture. Further research is needed to test the isolate potency as plant pathogenic biocontrol and plant growth inducer.